Investigating the Factors Influencing Literacy Skills among Young Students in Rural Areas of Indonesia - Nurcahyoko, Kunto; Anniurwanda, Pradipta; Sudirjo, Emilius (Language Circle: Journal of Language and Literature, 2024)
This study aims to analyze several factors influencing elementary school students’ literacy skills in rural regions of Indonesia. By employing a mixed-method design, the study combined quantitative and qualitative measures to identify the determinants of students’ literacy skills. The quantitative data were collected through questionnaires on factors related to literacy skills involving 852 grade six elementary school students from thirty-nine (39) public and private elementary schools in one of the rural areas in Indonesia. Descriptive statistics and T-tests were administered to analyze the questionnaire data and to identify the most and least significant factors and domains influencing students’ literacy skills. Additionally, qualitative data were gathered through semi-structured interviews with the participants. The results show that motivation and literacy facilities at schools and homes are crucial for students’ literacy development in rural areas. The discussion exhibits the role of literacy facilities and students’ motivation as dominant factors in shaping students’ literacy skills. This research contributes to understanding the factors influencing literacy skills among young learners in rural areas of Indonesia. The findings have implications for educators, educational institutions, parents, and policymakers, providing insights to shape educational policies and practices that enhance literacy outcomes in rural regions.